2010
DOI: 10.1039/b918164d
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic control of phase separation structures in nanoparticles of polymer blends

Abstract: This paper reports static and dynamic control of the phase separation structures of polymer blended nanoparticles. The phase separated nanoparticles were prepared from various combinations of polymers by evaporating good solvents from the polymer blended solutions after adding poor solvents into the solutions. Transmission electron microscope observation of the nanoparticles shows that two types of phase separation structures were formed in them. One is Janus type structure and another is core-shell type struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 20 publications
4
56
1
Order By: Relevance
“…A clear Janus structure is observed. As shown in a previous report, 26 PS and PI have similar solubility parameters; thus, these two polymers simultaneously precipitate as blend particles into the poor solvent. After precipitation, a Janus-type phase separation structure spontaneously forms to minimize the interface between the two phases.…”
Section: Hierarchical Assembly Of Cds Nanoparticles H Yabu Et Almentioning
confidence: 88%
See 1 more Smart Citation
“…A clear Janus structure is observed. As shown in a previous report, 26 PS and PI have similar solubility parameters; thus, these two polymers simultaneously precipitate as blend particles into the poor solvent. After precipitation, a Janus-type phase separation structure spontaneously forms to minimize the interface between the two phases.…”
Section: Hierarchical Assembly Of Cds Nanoparticles H Yabu Et Almentioning
confidence: 88%
“…[20][21][22][23][24][25] Recently, it was reported that the inner structure of polymer blend particles could be controlled by the hydrophobicity of blended polymers. 26 We have also found that block copolymer-stabilized Au nanoparticles can be introduced into polymer blend particles by the self-organized precipitation method. 27,28 In this report, we describe the control of a special arrangement of CdS nanoparticles in submicron-sized polymer particles by using the self-assembly of polymer blends and block copolymers.…”
Section: Introductionmentioning
confidence: 93%
“…The homopolymers were dissolved in THF, and water was used as a poor solvent. A coreshell phase separation structure was observed in the blend of particles comprising PI and poly(isobutylene) (PIB), 34 which is a more hydrophobic polymer than PI. In this case, PIB formed the core parts, and PI the shell parts.…”
Section: Award Accountsmentioning
confidence: 99%
“…Motoyoshi et al [ 36 ] prepared various composite nanoparticles by mixing two polymers in tetrahydrofuran (THF), dropping the solution in water, and then evaporating the THF. The difference between the Flory-Huggins solubility parameter ( ÎŽ ) for the two polymers infl uenced the morphologies of nanoparticles.…”
Section: Encapsulation Of Pib By Pvfmentioning
confidence: 99%